Effect of zinc on sputum conversion time of drug sensitive tuberculosis patients in Naypyitaw Union Territory: a quasi-experimental study - Thu, Si; Soe, Le T.; Mon, Aye S.; Lwin, Swe M. M.; Kyaw, Aung T.; Kyi, Myo S. (International Journal Of Community Medicine And Public Health, 2025)
Background: Tuberculosis (TB) remains a major global health problem, particularly in high-burden countries such as Myanmar. Malnutrition and zinc deficiency are common among TB patients and may impair immune response. Zinc supplementation has been proposed as an adjunct to standard anti-TB treatment to accelerate sputum conversion, but evidence remains inconsistent. Methods: A quasi-experimental study was conducted from January 2024 to December 2025 in Naypyitaw territory, Myanmar, enrolling 310 newly diagnosed drug-sensitive tuberculosis patients. Participants in one district received standard anti-TB therapy plus zinc supplementation (20 mg daily), while those in another district received standard therapy alone. Data on socio-demographic, clinical, behavioral, and health belief variables were collected. Survival analysis and Cox proportional hazards regression with propensity score adjustment was used to compare sputum conversion times between groups. Results: Zinc supplementation significantly improved sputum conversion time, with 72.9% reaching conversion earlier than 41.9% in the control group (adjusted hazard ratio [aHR]=1.93; 95% CI: 1.31–2.85; p=0.001). Additional factor positively influencing early sputum conversion was initial sputum grading. The findings indicated that zinc supplementation accelerates sputum smear conversion, likely by enhancing host immune defense. Conclusions: The findings underscored the critical roles of nutritional support in influencing treatment outcomes. Integrating zinc into TB treatment protocols, particularly among malnourished populations, represented a cost-effective and feasible strategy to enhance early microbiological response, improve clinical recovery, and potentially reduce TB transmission risk.